PHYTOCHEMICAL SCREENING AND BIOACTIVITY OF CHLOROFORM, ACETONE AND ETHYL ACETATE EXTRACTS OF HAEMATOSTAPHIS BARTERI - Ushie, A. O.; Abeng, F. E.; Azuaga, T. I.; Donatus, R. B.; Ama, S. O.; Aikhoje, E. F. (FUDMA JOURNAL OF SCIENCES, 2023)
The plant Haematostaphis barteri is commonly used traditionally for the treatment of diarrhoea, wound, headache, malaria, dysentery and fevers. The aim of this work was to carry out the phytochemical screening and antimicrobial activities chloroform, acetone and ethyl acetate extracts of H. barteri. The results showed that flavonoids, terpenes, terpenes, tannins, and saponins are detected in all the leaf extracts. The result of the antimicrobial activity obtained from the chloroform, acetone and ethyl acetate extracts of the leaf of H. barteri revealed that all the crude extracts chloroform, acetone and ethyl acetate leaf extracts exhibited antibacterial activity against Salmonella paratyphi, Staphylococcus aureus, Escherichia coli, and Penicillium spp. All the three extracts did not inhibit Aspergillus niger.